Comparison of the Intestinal Bacterial Flora in Healthy and Intestinal‐diseased Seahorses Hippocampus trimaculatus, Hippocampus erectus, and Hippocampus spinosissimus. Issue 3 (June 2015) - Li, Feng; Wang, Kai; Luo, Wei; Huang, Liangmin; Lin, Qiang
Abstract This investigation examined the intestinal microbial flora among healthy and intestinal‐diseased seahorses Hippocampus trimaculatus, Hippocampus erectus, and Hippocampus spinosissimus by utilizing polymerase chain reaction‐denaturing gradient gel electrophoresis (DGGE) and densitometric analysis. Results demonstrated that 16 disparate DGGE bands belong to six major bacterial groups, which were Vibrionace, Enterobacteriacea, Rhodobacteraceae, Sphingomonadaceae, Flavobacteriaceae, and Alcaligenaceae. It was found that Vibrionaceae was the dominant population among the healthy and intestinal‐diseased seahorses. Vibrio ponticus strain XJ3 and Vibrio neptunius strain WT82, especially V. ponticus strain XJ3 of high abundance, were identified for the first time in seahorses and concluded to be intestinal disease pathogens because of their co‐existence in three intestinal‐diseased seahorse species and other reported fish or oyster. In comparison, uncultured bacterium clone Alcaligenaceae, Vibrio sp., uncultured bacterium clone Rhodobacteraceae, Serratia nematodiphila strain, and Serratia marcescens strain comprised the basic intestinal bacterial flora of all healthy seahorses. This study is the first to report the presence of S. nematodiphila in seahorses.